Comparative Study of Marshall Properties and Durability of Superpave Pavements Using Pen 60/70 and Starbit Pg-70 Binding Materials with Fly Ash - Rahman, Indriasti Yustika (Diponegoro University, 2024)
The challenges of increasing vehicle volume and extreme loads need to be anticipated through pavement materials, both for gradations and bonding materials. This paper presents a comparative study of Marshall properties and durability of Superpave pavements using Starbit Pg-70 and Pen 60/70 binder materials with Fly Ash substitution. The laboratory experiment begins with physical testing of aggregate and bitumen materials, then determines of optimum bitumen content for each of the mixture with 0%, 50%, and 100% substitution for each type of binding material. A series of tests are carried out in the form of Marshall Standards and Index of Retained Strength (IRS), Indirect Tensile Strength (ITS), Tensile Strength Ratio (TSR), and Wheel Tracking at each optimum bitumen content. The results show that, in general, the use of Starbit Pg-70 binder has much better Marshall performance in terms of stability and Marshall quotient. Substitution of Fly Ash as Filler is also able to improve mechanical performance, with the advantage of increasing the value of Marshall Stability. Fly Ash fills the voids, so it has strong interlocking properties.